High efficacy bioconversion of starch to lactic acid using an amylolytic lactic acid bacterium isolated from Thai indigenous fermented rice noodles - Kanpiengjai,A. (Springer Netherlands, 2015)
© 2014, The Korean Society of Food Science and Technology and Springer Science+Business Media Dordrecht. Amylolytic lactic acid bacterium (ALAB) strain S21 was isolated from Thai indigenous fermented rice noodles and identified as Lactobacillus plantarum, based on 16S rDNA sequence and recA gene analysis. L. plantarum S21 exhibited a specific growth rate (μ) of 0.24 1/h in modified MRS broth containing 10 g/L of starch as the sole carbon source, and a high efficacy in producing lactic acid (9.41, 24.48, 41.84, 74.33, and 94.04 g/L from 10, 25, 50, 75, and 100 g/L of cassava starch, respectively), which are higher values than previously reported for ALAB. Crude amylase from L. plantarum S21 had broad pH stability (3.5–8.0), and hydrolyzed starch to maltose and glucose as the major and minor products. L. plantarum S21 should be considered useful for industrial bioconversion of starch to lactic acid.